Chondrocranium and skeletal development of Phrynops hilarii (Pleurodira: Chelidae) - Bona, Paula (2008)
The present study represents the first comprehensive contribution to the knowledge of the skeletal development of a pleurodiran turtle, Phrynops hilarii (Pleurodira, Chelidae). The most remarkable features found are: (1) absence of ascending process on pterygoquadrate cartilage; (2) presence of ossification centres for the epiotics; (3) as in other pleurodirans, dorsal ribs IX and X are ‘sacralized’; (4) contact between ilium and carapace occurs later in ontogenetic development; (5) suture between ischia, pubes and plastron occurs in posthatching specimens; (6) contrary to previous interpretations, the phalangeal formula of the pes of P. hilarii is 2 : 3 : 3 : 3 : 5; (7) the hooked bone represents the fifth metatarsal.